NKp30 Receptor Upregulation in Salivary Glands of Sjögren’s Syndrome Characterizes Ectopic Lymphoid Structures and Is Restricted by Rituximab Treatment - Pontarini, Elena; Sciacca, Elisabetta; Grigoriadou, Sofia; Rivellese, Felice; Lucchesi, Davide; Fossati-Jimack, Liliane; Coleby, Rachel; Chowdhury, Farzana; Calcaterra, Francesca; Tappuni, Anwar; Lewis, Myles J.; Fabris, Martina; et al. (Frontiers in Immunology, 2021)
Primary Sjögren’s syndrome (pSS) is a chronic autoimmune disease resulting from the inflammatory infiltration of exocrine glands, mainly salivary and lacrimal glands, leading to secretory dysfunction and serious complications including debilitating fatigue, systemic autoimmunity and lymphoma. Like other autoimmune disorders, a strong interferon (IFN) signature is present among subsets of pSS patients, suggesting the involvement of innate immunity in pSS pathogenesis. NCR3/NKp30 is a natural killer (NK) cell –specific activating receptor regulating the cross talk between NK and dendritic cells including type II IFN secretion upon NK-cell activation. A genetic association between single nucleotide polymorphisms (SNPs) in the NCR3/NKp30 promoter gene and a higher susceptibility for pSS has been previously described, with pSS patients most frequently carrying the major allele variant associated with a higher NKp30 transcript and IFN-γ release as consequence of the receptor engagement. In the present study we combined RNA-sequencing and histology from pSS salivary gland biopsies to better characterize NKp30 (NCR3) and its ligand B7/H6 (NCR3LG1) in pSS salivary gland tissues. Levels of NCR3/NKp30 were significantly increased both in salivary glands and in circulating NK cells of pSS patients compared with sicca controls, especially in salivary glands with organized ectopic lymphoid structures. In line with this observation, a strong correlation between NCR3/NKp30 levels and salivary gland infiltrating immune cells (CD3, CD20) was found. Furthermore, NCR3/NKp30 levels also correlated with higher IFN-γ, Perforin and Granzyme-B expression in pSS SGs with organized ectopic lymphoid structures, suggesting an activation state of NK cells infiltrating SG tissue. Of note, NKp30+ NK cells accumulated at the border of the inflammatory foci, while NKp30 ligand, B7/H6, showed to be expressed mainly by ductal epithelial cells in pSS salivary glands. Finally, immunomodulatory treatment, such as the B-cell depleting agent rituximab, known to reduce the infiltration of immune cells in pSS SGs, prevented the up-regulation of NCR3/NKp30 within the glands.